ISH ADA-01 Critical role of telomerase in regulating cerebral vascular function and redox environment. (September 2016) - Ait-Aissa, Karima; Hockenberry, Joseph; Gutterman, David; Geurts, Aron; Beyer, Andreas
Abstract : Objective: Flow mediated dilation (FMD) is the most physiological relevant form of endothelial-mediated vasodilation. Our laboratory has previously shown that telomerase, a ribo-nucleoprotein that counteracts telomere shortening, has a protective effect on endothelial function under conditions of oxidative stress in the human microcirculation. In the presence of coronary artery disease, decreased telomerase activity contributes to a shift in the mediator of FMD from atheroprotective nitric oxide (NO) to pro-inflammatory and atherogenic hydrogen peroxide (H2 O2 ). Endothelial dysfunction in the cerebral vasculature has been directly linked to cerebral microbleeds and cognitive decline in models of stroke and dementia, thus we hypothesized that TERT plays a critical role in maintaining normal NO-mediated vasodilation in the cerebral vasculature. Design and Method: Using Crisp/Cas9 we generated a novel deletion model for TERT (the catalytic subunit of telomerase) in rats on the WKY background. Middle cerebral arteries (MCA) were isolated from wildtype (WT) and TERT −/− rats, prepared for videomicroscopy, and FMD was measured. The mediator of FMD was determined using a pharmacological inhibitor of NO-synthase (L-NAME) and a scavenger of H2 O2 (PEG-catalase). Results: No changes in the magnitude of FMD were observed in MCA from TERT −/− compared to WT rats (max dilation: TERT −/− 71.97 ± 14.7% vs. WT 80.9 ± 10.6%; n≥3; p > 0.05 two way ANOVA RM). In WT animals, pre-incubation with L-NAME abolished FMD while PEG-catalase had no effect on FMD (max dilation: L-NAME -5.8 ± 7%; Peg-catalase 76.6 ± 8.6%; n≥3; p < 0.05). Conversely, in TERT −/− animals FMD was not affected in the presence of L-NAME but abolished in presence of Peg-catalase (max dilation: L-NAME 57.8.0 ± 16.5%; Peg-catalase −4.3 ± 2.4%; n≥3; p < 0.05). Conclusions: Telomerase deficiency causes a switch in the vasoactive mediator of FMD from NO to H2 O2, creating a pro-oxidative environment in the cerebral vasculature. Understanding the regulatory role of telomerase in mediating this mechanistic switch may provide a novel therapeutic strategy for the treatment or prevention of cerebrovascular dysfunction.